Body mass index and arterial stiffness are associated with greater beat-to-beat blood pressure variability after transient ischemic attack or minor stroke - Webb, AJS; Lawson, A; Mazzucco, S; Li, L; Rothwell, PM (Wolters Kluwer, 2021)
Background and Purpose: Blood pressure variability (BPV) from beat to beat is associated with an increased risk of cardiovascular events and enables rapid assessment of BPV, but the underlying causes of elevated BPV are unclear. Methods: In consecutive patients within 4 to 6 weeks of transient ischemic attack or nondisabling stroke (OXVASC [Oxford Vascular Study]), continuous noninvasive blood pressure was measured beat to beat over 5 minutes (Finometer). Arterial stiffness was measured by carotid-femoral pulse wave velocity (Sphygmocor). After automated and manual data cleaning, associations between BPV (residual coefficient of variation), demographic factors, and arterial stiffness were determined for both systolic and diastolic blood pressure, by ANOVA and linear models. Relationships between demographic factors and arterial stiffness were determined by interaction terms and mediation. Results: Among 1013 patients, 54 (5.3%) were in AF, and 51 (5%) had low-quality recordings. In a general linear model including the remaining 908 participants, systolic BPV (SBPV) was most strongly associated with age (P=0.00003), body mass index (BMI; P=0.003), and arterial stiffness (P=0.008), with weaker independent associations with current smoking (P=0.01) and a low diastolic blood pressure (P=0.046). However, while there was a linear increase in SBPV with BMI in men, in women, SBPV was lowest for a BMI in the normal range but was greater below 20 or above 30 (ANOVA, P=0.012; BMI-sex interaction, P=0.03). Although BMI and pulse wave velocity were partially independent, increased pulse wave velocity mediated ≈32% of the relationship between increased BMI and SBPV (P<0.001). Conclusions: Vascular aging, manifest as arterial stiffness, was a strong determinant of increased SBPV and partially mediated the effect of increased BMI. However, although high BMI was independently associated with SBPV in both sexes, a low BMI was associated with increased SBPV only in women. SBPV may partially mediate the relationship between BMI and cardiovascular events, while obesity may provide a modifiable target to reduce SBPV and cardiovascular events.